Effects of High Hydrostatic Pressure Processing on the Number of Bacteria and Texture of Beef Liver - Hirokazu Ogihara; Hodaka Suzuki; Masaki Michishita; Hitoshi Hatakeyama; Yumiko Okada (Journal of Food Quality)
Providing beef liver for raw consumption was banned in Japan on July 1, 2012. To lift the ban, the establishment of effective countermeasures for safe raw consumption is necessary. In this study, we examined the effects of high hydrostatic pressure processing on raw beef liver. Beef liver samples subjected to 300 MPa of pressure or higher for 10 min at 25°C became firmer and showed a paler color and were considered unsuitable for raw consumption. More than 3.0 log reductions of bacteria were seen after treatments at 400 and 500 MPa, but the treatment with lower pressure did not show enough microcidal effects for safe consumption. Histological and ultrastructural analysis revealed that high hydrostatic pressure processing increased mitochondrial swelling and reduced rough endoplasmic reticula in hepatocytes, and such changes might be related to the observed changes of texture in the treated raw beef liver.